Complex Multisystem Phenotype With Immunodeficiency Associated With NBAS Mutations: Reports of Three Patients and Review of the Literature - Khoreva, Anna; Pomerantseva, Ekaterina; Belova, Natalia; Povolotskaya, Inna; Konovalov, Fedor; Kaimonov, Vladimir; Gavrina, Alena; Zimin, Sergey; Pershin, Dmitrii; Davydova, Nataliia; Burlakov, Vasilii; Viktorova, Ekaterina; et al. (Frontiers in Pediatrics, 2020)
OBJECTIVES: Mutations in the neuroblastoma-amplified sequence (NBAS) gene were originally described in patients with skeletal dysplasia or isolated liver disease of variable severity. Subsequent publications reported a more complex phenotype. Among multisystemic clinical symptoms, we were particularly interested in the immunological consequences of the NBAS deficiency. METHODS: Clinical and laboratory data of 3 patients ages 13, 6, and 5 in whom bi-allelic NBAS mutations had been detected via next-generation sequencing were characterized. Literature review of 23 publications describing 74 patients was performed. RESULTS: We report three Russian patients with compound heterozygous mutations of the NBAS gene who had combined immunodeficiency characterized by hypogammaglobulinemia, low T-cells, and near-absent B-cells, along with liver disease, skeletal dysplasia, optic-nerve atrophy, and dysmorphic features. Analysis of the data of 74 previously reported patients who carried various NBAS mutations demonstrated that although the most severe form of liver disease seems to require disruption of the N-terminal or middle part of NBAS, mutations of variable localizations in the gene have been associated with some form of liver disease, as well as immunological disorders. CONCLUSIONS: NBAS deficiency has a broad phenotype, and referral to an immunologist should be made in order to screen for immunodeficiency.